PENGEMBANGAN SMART DOOR LOCK BERBASIS IOT UNTUK MONITORING AKSES KARYAWAN DI PT EKASA TEKNOLOGI NUSANTARA - Bagaskara, Aditya; Pradana, Afu Ichsan; Hartanti, Dwi (Infotech: Journal of Technology Information, 2025)
Traditional physical door locks have various limitations, including the risk of loss, unauthorized duplication, and the inability to log access in real time. In a dynamic work environment such as PT Ekasa Teknologi Nusantara, this poses potential security risks to valuable company assets. A more flexible, efficient, and digitally monitored security system is therefore required. This study aims to design an Internet of Things (IoT)-based Smart Door Lock system capable of automatically recording and managing access. The method used involved observation of employee access patterns and the Agile software development approach, consisting of planning, design, development, testing, deployment, review, and launch phases. The system was developed using an ESP32 microcontroller, RFID module, and solenoid lock, all integrated with a user interface for managing access data. Testing results showed that the system can log entry activity in real time, send notifications, and provide management with flexibility in granting or revoking access rights. Thus, the system enhances company asset security, reduces reliance on physical keys, and offers an adaptive digital solution for workspace access control. The system also has potential for further development to meet organizational needs.